A cross sectional study on willingness and acceptabily: PPIUCD by primipara mothers at a tertiary care hospital, Tamil Nadu - Shaanthy Gunasingh, T. K.; Meena, T. S.; Mothilal, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Postpartum intrauterine contraceptive device is a postpartum family planning method which provides spacing to the next pregnancy and also it helps to avoid unwanted / unintended pregnancy during postpartum period. Our aim was to study the willingness and acceptability of Postpartum intrauterine contraceptive device among primi paraous women and compare them as a factor of route of insertion (vaginal versus caesarean). Methods: A cross sectional analytical study was done in a tertiary care teaching institution to know the willingness and acceptance among primi paraous delivery (either vaginal and caesarean deliveries) for the period of three months using the hospital records that a total number of 587 primi paraous deliveries and among them 433 mothers had Postpartum intrauterine contraceptive device over the three months period, were taken as a secondary data and studied for their willingness and acceptance for Postpartum intrauterine contraceptive device. Results: 82.8 % of primi paraous women were showing willingness for Postpartum intrauterine contraceptive device and 73.8 % of them had Postpartum intrauterine contraceptive device insertion. Postpartum intrauterine contraceptive device insertions were more in caesarean deliveries than in vaginal deliveries of mothers with one child. Conclusions: Postpartum intrauterine contraceptive device is a strong weapon in the family planning and should be encouraged in both vaginal and caesarean deliveries. The acceptability of Postpartum intrauterine contraceptive device in women with one child was effective and statistically significant at p value is < 0.05.